2021
DOI: 10.1007/s10935-021-00643-2
|View full text |Cite
|
Sign up to set email alerts
|

Health Information Source Characteristics Matter: Adapting the Dissemination of an HPV Vaccine Intervention to Reach Latina and Vietnamese Women

Abstract: Latina and Vietnamese women are disproportionately burdened by human papillomavirus (HPV)-associated cervical cancer and underutilize the HPV vaccine, which is an effective cancer prevention measure. To inform the adaptation of a National Cancer Institute’s evidence-based cancer control program, HPV Vaccine Decision Narratives, and because of the rapidly changing information concerning consumption patterns of young adults, we elicited preferences and characteristics associated with women’s interest in various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…For example, community-based organizations were emphasized as important sources of information in the AI/AN focus group, and both AI/AN and Spanish focus group expressed desire for adolescent-directed school-based resources. Other literature supports that information source characteristics and cultural adaptation of content is needed to optimize dissemination of HPV vaccine interventions in diverse ethnic communities [ 40 42 ]. However, we observed that racial/ethnic minority parents not only had preferred channels of information but relied on their trusted sources and personal relationships with health care providers and family and friends to navigate the proliferation of adolescent vaccine misinformation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, community-based organizations were emphasized as important sources of information in the AI/AN focus group, and both AI/AN and Spanish focus group expressed desire for adolescent-directed school-based resources. Other literature supports that information source characteristics and cultural adaptation of content is needed to optimize dissemination of HPV vaccine interventions in diverse ethnic communities [ 40 42 ]. However, we observed that racial/ethnic minority parents not only had preferred channels of information but relied on their trusted sources and personal relationships with health care providers and family and friends to navigate the proliferation of adolescent vaccine misinformation.…”
Section: Discussionmentioning
confidence: 99%
“…Social media offers a communication tool for disseminating and interacting with youth and young adults about HPV vaccination, given their daily message exposure on these platforms (85)(86)(87). Preventing cancers caused by HPV through vaccination remains a significant public health priority in the United States (16).…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al (2014) also found that business managers consider time, cost and effort in information-seeking to avoid investing excessive time and effort. Majid and Kanagasabai (2007), Hopfer et al (2021) and Obaremi and Olatokun (2022) also found that ease of access, ease of use and convenience were criteria for users' information source preferences. Hence, users would consider the cost of information-seeking when selecting an information source.…”
Section: Context Of Information Source Preferences Researchmentioning
confidence: 94%
“…For example, American college students employed the fluidity of information as a preference criterion when seeking information during the pandemic (Stewart, 2022). Latin and Vietnamese women seeking health information select sources based on their immediacy, thereby avoiding information overload (Hopfer et al, 2021). Furthermore, the users were concerned about whether the information source was interactive and responsive.…”
Section: Context Of Information Source Preferences Researchmentioning
confidence: 99%